The Bahr al-Madhi of Shaykh Muhammad Idris Al-Marbawi: A Preliminary Analysis - Muhammad Mustaqim Mohd.Zarif (Universiti Sains Islam Malaysia, 2024)
The Bahr al-Madhi of Shaykh Muhammad Idris al-Marbawi can be aptly considered as one of the greatest literary masterpiece of Malay Muslim scholarship in the twentieth century. It was composed as a commentary to the Jami' al-Tirmidhi and the only one of its kind to have been written in the Malay language. Perhaps, due to the lack of awareness, the book has not received attention or been the subject of any study or scrutiny by contemporary researchers. It is therefore, the intention of this preliminary exposition on the book in terms of its scope, content and analysis of the methodology of its author to pave the way for further analysis and studies in the future.